On the complex nature of speech kinematics - Fuchs, Susanne; Perrier, Pascal (ZAS Papers in Linguistics, 2005)
Studying kinematic behavior in speech production is an indispensable and fruitful methodology in order to describe for instance phonemic contrasts, allophonic variations, prosodic effects in articulatory movements. More intriguingly, it is also interpreted with respect to its underlying control mechanisms. Several interpretations have been borrowed from motor control studies of arm, eye, and limb movements. They do either explain kinematics with respect to a fine tuned control by the Central Nervous System (CNS) or they take into account a combination of influences arising from motor control strategies at the CNS level and from the complex physical properties of the peripheral speech apparatus. We assume that the latter is more realistic and ecological. The aims of this article are: first, to show, via a literature review related to the so called '1/3 power law' in human arm motor control, that this debate is of first importance in human motor control research in general. Second, to study a number of speech specific examples offering a fruitful framework to address this issue. However, it is also suggested that speech motor control differs from general motor control principles in the sense that it uses specific physical properties such as vocal tract limitations, aerodynamics and biomechanics in order to produce the relevant sounds. Third, experimental and modelling results are described supporting the idea that the three properties are crucial in shaping speech kinematics for selected speech phenomena. Hence, caution should be taken when interpreting kinematic results based on experimental data alone.